Stayin' alive - N-Trance; O'Toole, Kevin; Longworth, Dale; AATW Productions (United Kingdom : AATW Productions, 1995)
Contains five tracks taken from the album Elecronic Pleasure.
CD 1 : Stayin' Alive (radio version) -- I Will Take You There -- Turn Up The Power (dark mix) -- Stayin' Alive (long version) -- Set You Free (original radio edit).
Koleksi Khas Wiramanja.
Featuring Ricardo Da Force.
Keywords: Songs, English; Disco music